2016
DOI: 10.1080/21655979.2016.1197632
|View full text |Cite
|
Sign up to set email alerts
|

Influence of static electric field on cognition in mice

Abstract: With the rapid development of high voltage direct current transmission, the possibility of health effects associated with static electric field (SEF) has caused wide public concern. To examine the effects of long-lasting, full-body exposure to SEF on cognition, Institute of Cancer Research mice were exposed to SEF for 35 d. The intensities of SEF in experimental group I (EG-I), experimental group II (EG-II) and control group (CG) were 2.30∼15.40 kV/m, 9.20∼21.85 kV/m and 0 kV/m, respectively. The performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In order for electrostatic fields to be used as a repellent, it necessarily exposes the person using it to the fields. While there have been concerns about the potential harmful effects of high electric fields on humans, these appear to be inconclusive or miniscule [37,39,40]. The only small risk of static electric fields are micro-shocks, which only cause a minor nuisance and have no real adverse effects [37,41].…”
Section: Resultsmentioning
confidence: 99%
“…In order for electrostatic fields to be used as a repellent, it necessarily exposes the person using it to the fields. While there have been concerns about the potential harmful effects of high electric fields on humans, these appear to be inconclusive or miniscule [37,39,40]. The only small risk of static electric fields are micro-shocks, which only cause a minor nuisance and have no real adverse effects [37,41].…”
Section: Resultsmentioning
confidence: 99%
“…Four of these studies examined various neurotransmitter concentrations in the brains of rodents, but the results were inconsistent [ 38 , 40 , 56 , 57 ]. Möse et al [ 56 ] reported significantly reduced serotonin levels in the brain of guinea pigs that had been exposed to a static EF (23.8 kV/m for 6 days).…”
Section: Resultsmentioning
confidence: 99%
“…Bailey and Charry [ 38 ] and Charry and Bailey [ 40 ] reported that norepinephrine, dopamine and serotonin concentrations were not affected in rats’ brains after the animals were exposed to a static EF (3 kV/m for 2,18 or 66 h). Xu et al [ 57 ] tested spatial learning and memory abilities of mice previously exposed to a static EF (between 2.3 and 21.85 kV/m for 35 days) beneath a HVDC line in the ambient environment. They did not find changes in glutamate and GABA levels which have been associated with learning and memory abilities in some other studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations